Preparation method of titanium alloy coating on surface of steel base material
Through the improved preparation method of titanium alloy coating on the surface of steel substrates, laser cladding and mechanical processing technology, the problems of high cost of titanium alloy products and poor coating flatness are solved, and low cost, corrosion resistance and wear resistance are achieved titanium alloy coating preparation.
Patent Information
- Application Number
- CN202411704136.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The production process of existing titanium alloy products is high, and the titanium alloy coating cannot be completely fused with the substrate, resulting in surface flatness problems.
Using the improved preparation method of titanium alloy coating on the surface of steel substrate, the copper transition layer and titanium alloy coating are prepared by preparing titanium alloy powder, pretreatment of steel substrates, and laser cladding method under argon protection, and the copper transition layer and titanium alloy coating are prepared. Machined to polish the cladding.
It has achieved low-cost preparation of titanium alloy coatings, good fusion of the coating and the substrate, improved surface flatness, excellent corrosion resistance and wear resistance, and salt spray resistance up to 3000h.
Smart Images

Figure CN119433534A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser cladding, in particular to a method for preparing a titanium alloy coating on the surface of a steel substrate. Background Art
[0002] Applying an appropriate coating on the surface of the steel substrate is an effective way to slow down the occurrence of corrosion. Titanium metal, as a lightweight, high-strength structural material, has excellent immunity to the erosion of seawater and marine atmospheric environment, and is an important strategic metal material in the field of marine engineering equipment. However, most titanium alloy products on the market currently use the traditional production process of smelting-forging-machining, and the high cost greatly limits the application of titanium alloys.
[0003] At the same time, the existing preparation method makes it impossible for the titanium alloy coating and the substrate body to be fully fused, resulting in defects and causing quality problems in the flatness of the surface of the cladding layer.
[0004] Therefore, the market is in urgent need of a new method for preparing titanium alloy coatings on the surface of steel substrates to reduce costs and produce excellent titanium alloy coatings based on steel substrates. Summary of the invention
[0005] The purpose of the present invention is to provide an improved method for preparing a titanium alloy coating on the surface of a steel substrate. Through the improvement of the process, the prepared titanium alloy coating on the surface of the steel substrate has excellent corrosion resistance and excellent wear resistance.
[0006] In order to achieve the above-mentioned purpose, the technical scheme of the present invention is: a method for preparing a titanium alloy coating on the surface of a steel substrate, characterized in that: the preparation method comprises the following steps: a. preparing titanium alloy powder; b. pretreating the steel substrate; polishing the surface of the steel workpiece, and then ultrasonically cleaning it with clean water and ethanol for 20-25 minutes respectively, and then blowing it dry and preheating it in advance; c. using a binder to evenly coat the tin bronze powder on the surface of the steel substrate; d. under the protection of argon gas, using laser cladding to prepare a copper transition layer on the surface of the steel substrate, and then using mechanical processing to grind the surface of the cladding layer flat; e. using a binder to evenly coat the titanium alloy powder on the surface of the material treated in step d; f. under the protection of argon gas, using a laser cladding method to prepare a titanium alloy coating on the surface of the steel substrate; using mechanical processing to grind the surface of the cladding layer flat to complete the preparation of the titanium alloy coating.
[0007] Preferably, in step a, the titanium alloy powder is prepared from raw materials with the following weight percentages: Ni 40-50%, Fe 8-10%, Co 5-10%, Cr 5-10%, Nb 5-10%, and the balance is Ti; the solvent is weighed according to the above raw material ratios and placed in a dispersion tank, slowly stirred, and then a binder is added until dissolved; metal powders of Ni, Fe, Co, Cr, Nb, and Ti are added in sequence according to the above ratios, high-speed grinding and dispersion for 20-30 minutes, and drying treatment is carried out at 120°C for more than 2 hours to obtain a titanium alloy powder with a powder diameter between 45 and 105 μm.
[0008] Furthermore, in step b, during the steel surface pretreatment, the workpiece surface is polished and cleaned using sandpapers of 100 mesh, 150 mesh, 250 mesh, 400 mesh and 600 mesh in sequence; and the steel substrate is preheated to 200°C.
[0009] Furthermore, in step c, the tin bronze powder with a powder diameter of 50 to 100 μm is dried at 120° C. for more than 2 hours, and then the tin bronze powder is coated on the surface of the steel substrate using a polyvinyl alcohol adhesive.
[0010] Furthermore, in step d, in the laser cladding process, the laser beam is scanned vertically, and argon is blown laterally for protection during the scanning process, and argon is blown coaxially to protect the lens barrel; the process parameters are: laser power 0.75-1.2KW, scanning speed 2.5-3.5mm / s, spot diameter 4mm, the distance from the laser mirror to the surface of the titanium alloy sample is 100mm, and the argon protection gas pressure is 0.3-0.7MPa.
[0011] Furthermore, in step e, the titanium alloy powder is evenly coated on the surface of the steel substrate using a polyvinyl alcohol adhesive. In step f, in the laser cladding process, the laser beam is scanned vertically, and argon gas is blown laterally for protection during the scanning process, and argon gas is coaxially blown to protect the lens barrel. The process parameters are: laser power 0.75-1.5KW, scanning speed 2.5-4.5mm / s, spot diameter 4mm, the distance from the laser mirror to the surface of the titanium alloy sample is 100mm, and the argon gas protection pressure is 0.4-0.7MPa.
[0012] Furthermore, in step a, high-speed grinding and dispersion is performed using a planetary ball mill with a rotation speed of 1000-1500 rpm.
[0013] Compared with the prior art, the technical solution of the present invention not only improves the overall technical solution, but also includes many improvements in details. Specifically, it has the following beneficial effects:
[0014] 1. The improved scheme of the present invention uses titanium alloy powder and tin bronze powder as main raw materials, is protected by argon gas, and a titanium alloy laser cladding layer is prepared by two laser cladding methods. The prepared titanium alloy coating on the surface of the steel substrate has excellent wear resistance and excellent corrosion resistance, and the salt spray resistance can reach 3000h;
[0015] 2. In the technical solution of the present invention, a copper transition layer is prepared on the surface of a steel substrate by laser cladding under argon protection, and then the surface of the cladding layer is polished and smoothed by mechanical processing;
[0016] Then, under the protection of argon gas, a titanium alloy coating is prepared on the surface of the steel substrate by laser cladding method; the surface of the cladding layer is polished and smoothed by mechanical processing to complete the preparation of the titanium alloy coating;
[0017] The titanium alloy coating has the advantages of small heat-affected zone, good bonding between cladding layer and substrate, dense cladding layer, and high applicability of integration into materials.
[0018] 3. The titanium alloy powder of the present invention is prepared from the following raw materials in weight percentage: Ni 40-50%, Fe 8-10%, Co 5-10%, Cr 5-10%, Nb 5-10%, and the balance is Ti. The application of this titanium alloy powder reduces the application cost of titanium alloy products and also improves the corrosion resistance of the material surface;
[0019] 4. The process steps of the present invention are clear and reasonable, easy to operate, and low in cost. It improves the corrosion resistance and wear resistance of the steel substrate and has great promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 1 is a metallographic image of a titanium alloy coating in one embodiment of the present invention. DETAILED DESCRIPTION
[0021] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The invention provides a method for preparing a titanium alloy coating on the surface of a steel substrate, which is different from the prior art in that: the preparation method comprises the following steps: a, preparing titanium alloy powder; b, pre-treating the steel substrate; polishing the surface of the steel workpiece, and then ultrasonically cleaning it with clean water and ethanol for 20-25 minutes respectively, and then blowing it dry to preheat it in advance; c, using a binder to evenly coat the tin bronze powder on the surface of the steel substrate; d, under the protection of argon, using a laser cladding method to prepare a copper transition layer on the surface of the steel substrate, and then using a mechanical processing method to grind the surface of the cladding layer flat; e, using a binder to evenly coat the titanium alloy powder on the surface of the material treated in step d; f, under the protection of argon, using a laser cladding method to prepare a titanium alloy coating on the surface of the steel substrate; using a mechanical processing method to grind the surface of the cladding layer flat to complete the preparation of the titanium alloy coating.
[0023] In practice, the following raw materials in weight percentage are firstly prepared: Ni 40-50%, Fe 8-10%, Co 5-10%, Cr 5-10%, Nb 5-10%, and the remainder is Ti, the total weight of which is 100%, into titanium alloy powder with a powder diameter between 45 and 105 μm.
[0024] Then, through two laser cladding methods (first preparing a copper transition layer and then preparing a titanium alloy coating), a titanium alloy coating on the surface of a steel substrate is finally obtained. The coating is fully fused with the substrate without defects, and the surface quality of the cladding layer is smooth. This titanium alloy coating has excellent corrosion resistance and can withstand salt spray for up to 3000 hours. It also has excellent wear resistance.
[0025] Example 1
[0026] In this embodiment, copper powder and titanium alloy powder are used as main raw materials and prepared by laser cladding method, including the following steps:
[0027] (1) Preparing titanium alloy powder; titanium alloy powder is prepared from the following raw materials in weight percentage: Ni40%, Fe8%, Co5%, Cr10%, Nb10%, Ti27%. Weigh deionized water solvent at 4% of the raw material weight percentage and place it in a dispersion tank, slowly stir it, and then add polyvinyl alcohol binder at 9% of the raw material weight percentage until it dissolves; add metal powders in proportion and grind and disperse them at high speed for 20 to 30 minutes; the high-speed grinding and dispersion adopts a planetary ball mill with a rotation speed of 1000-1500rpm. The powder has a diameter of 45 to 105μm and is dried at 120℃ for more than 2 hours. The deionized water solvent here is the prior art, which is a pure water that has been cleared of mineral ions (salts) such as sodium, calcium, iron, copper, chloride and bromide.
[0028] (2) Pre-treating the surface of the steel substrate; using 100 mesh, 150 mesh, 250 mesh, 400 mesh and 600 mesh sandpaper to polish the surface of the steel substrate workpiece, and then ultrasonically cleaning it with clean water and ethanol for 20-25 minutes respectively, and drying it; preheating it to 200°C in advance;
[0029] (3) using polyvinyl alcohol binder to evenly coat tin bronze powder on the surface of a steel substrate, wherein the powder diameter is between 50 and 100 μm, and drying is performed at 120° C. for more than 2 hours;
[0030] (4) Under argon protection, the copper transition layer was prepared by laser cladding, and the surface of the cladding layer was polished and smoothed by mechanical processing; the laser process parameters were: vertical scanning of the laser beam, and argon protection was blown laterally during the scanning process, and argon was blown coaxially to protect the lens barrel, the process parameters were: laser power 0.75KW, scanning speed 2.5mm / s, spot diameter 4mm, the distance from the laser mirror to the surface of the titanium alloy sample was 100mm, and the argon protection gas pressure was 0.3MPa;
[0031] (5) using a binder, polyvinyl alcohol, to uniformly coat the titanium alloy powder on the surface of the material after the first step of treatment;
[0032] (6) Under argon protection, titanium alloy coating was prepared by laser cladding; the laser process parameters were: vertical scanning of the laser beam, and argon protection was blown laterally during the scanning process, and argon was blown coaxially to protect the lens barrel. The process parameters were: laser power 0.75KW, scanning speed 2.5mm / s, spot diameter 4mm, the distance from the laser mirror to the surface of the titanium alloy sample was 100mm, and the argon protection gas pressure was 0.4MPa; the surface of the cladding layer was polished and smoothed by mechanical processing to obtain the titanium alloy coating.
[0033] The surface microstructure of the titanium alloy coating prepared in Example 1 can be intuitively analyzed through the metallographic image. It can be found that the interface of the prepared titanium alloy coating is well bonded, without obvious defects such as cracks and pores, see Figure 1 .
[0034] Example 2
[0035] In this embodiment, copper powder and titanium alloy powder are used as main raw materials and prepared by laser cladding method, including the following steps:
[0036] (1) Preparation of titanium alloy powder; titanium alloy powder is prepared from the following raw materials in weight percentage: Ni42%, Fe9%, Co6%, Cr8%, Nb8%, Ti27%. Deionized water is weighed according to 8% of the raw material weight percentage and placed in a dispersion tank, slowly stirred, and then 7% of the raw material weight percentage of the binder polyvinyl alcohol is added until dissolved; metal powders are added in proportion and dispersed at high speed for 20 to 30 minutes; the high-speed grinding and dispersion adopts a planetary ball mill with a rotation speed of 1000-1500rpm. The powder diameter is between 45 and 105μm, and it is dried at 120℃ for more than 2 hours.
[0037] (2) Pre-treating the surface of the steel substrate; using 100 mesh, 150 mesh, 250 mesh, 400 mesh and 600 mesh sandpaper to polish the surface of the steel substrate workpiece, and then ultrasonically cleaning it with clean water and ethanol for 20-25 minutes respectively, and drying it; preheating it to 200°C in advance;
[0038] (3) using a binder to evenly coat the tin bronze powder on the surface of the steel substrate, the powder diameter being between 50 and 100 μm, and drying the powder at 120° C. for more than 2 hours;
[0039] (4) Under argon protection, the copper transition layer was prepared by laser cladding, and the surface of the cladding layer was polished and smoothed by mechanical processing; the laser process parameters were: vertical scanning of the laser beam, and argon protection was blown laterally during the scanning process, and argon was blown coaxially to protect the lens barrel, the process parameters were: laser power 0.85KW, scanning speed 3.0mm / s, spot diameter 4mm, the distance from the laser mirror to the surface of the titanium alloy sample was 100mm, and the argon protection gas pressure was 0.4MPa;
[0040] (5) using a binder, polyvinyl alcohol, to uniformly coat the titanium alloy powder on the surface of the material after the first step of treatment;
[0041] (6) Under argon protection, titanium alloy coating was prepared by laser cladding; the laser process parameters were: vertical scanning of the laser beam, and argon protection was blown laterally during the scanning process, and argon was blown coaxially to protect the lens barrel. The process parameters were: laser power 1.0KW, scanning speed 3.0mm / s, spot diameter 4mm, distance from the laser mirror to the surface of the titanium alloy sample 100mm, argon protection gas pressure 0.5MPa; the surface of the cladding layer was polished and smoothed by mechanical processing. The prepared titanium alloy coating on the surface of the steel substrate has excellent wear resistance and excellent corrosion resistance, and can withstand salt spray for up to 3000h.
[0042] Example 3
[0043] In this embodiment, copper powder and titanium alloy powder are used as main raw materials and prepared by laser cladding method, including the following steps:
[0044] (1) Preparation of titanium alloy powder; titanium alloy powder is prepared from the following raw materials in weight percentage: Ni44%, Fe10%, Co8%, Cr6%, Nb6%, Ti32%. Deionized water is weighed according to 9% of the raw material weight percentage and placed in a dispersion tank, slowly stirred, and then 7% of the raw material weight percentage of the binder polyvinyl alcohol is added until dissolved; metal powders are added in proportion and dispersed at high speed for 20 to 30 minutes; the high-speed grinding and dispersion adopts a planetary ball mill with a rotation speed of 1000-1500rpm. The powder diameter is between 45 and 105μm, and it is dried at 120℃ for more than 2 hours.
[0045] (2) Pre-treating the surface of the steel substrate; using 100 mesh, 150 mesh, 250 mesh, 400 mesh and 600 mesh sandpaper to polish the surface of the steel substrate workpiece, and then ultrasonically cleaning it with clean water and ethanol for 20-25 minutes respectively, and drying it; preheating it to 200°C in advance;
[0046] (3) using a binder to evenly coat the tin bronze powder on the surface of the steel substrate, the powder diameter being between 50 and 100 μm, and drying the powder at 120° C. for more than 2 hours;
[0047] (4) Under argon protection, the copper transition layer was prepared by laser cladding, and the surface of the cladding layer was polished and smoothed by mechanical processing; the laser process parameters were: vertical scanning of the laser beam, and argon protection was blown laterally during the scanning process, and argon was blown coaxially to protect the lens barrel. The process parameters were: laser power 1.2KW, scanning speed 3.5mm / s, spot diameter 4mm, the distance from the laser mirror to the surface of the titanium alloy sample was 100mm, and the argon protection gas pressure was 0.7MPa;
[0048] (5) using a binder, polyvinyl alcohol, to uniformly coat the titanium alloy powder on the surface of the material after the first step of treatment;
[0049] (6) Under argon protection, titanium alloy coating was prepared by laser cladding; the laser process parameters were: vertical scanning of the laser beam, and argon protection was blown laterally during the scanning process, and argon was blown coaxially to protect the lens barrel. The process parameters were: laser power 1.5KW, scanning speed 4.5mm / s, spot diameter 4mm, the distance from the laser mirror to the surface of the titanium alloy sample was 100mm, and the argon protection gas pressure was 0.7MPa; the surface of the cladding layer was polished and smoothed by mechanical processing.
[0050] The microscopic morphology of the prepared titanium alloy coating was analyzed by metallographic microscope, and the hardness of the titanium alloy coating prepared in each embodiment was tested.
[0051] The prepared coating sample was immersed in a simulated seawater (3.5% NaCl) solution to test its corrosion resistance. The coating sample was used as the working electrode, the sample working area was 1 cm2, the saturated calomel electrode (SCE) was used as the reference electrode, the platinum electrode was used as the auxiliary electrode, the scanning speed was 2 mV / s, and the impedance (EIS) diagram and electrochemical polarization curve were measured on the electrochemical workstation. The self-corrosion potential (E coor ) and self-corrosion current density (I coor ).
[0052] Table 1 Self-corrosion potential and self-corrosion current of titanium alloy cladding layer in Examples 1 to 3
[0053] Alloy coating name <![CDATA[E SCE / mV]]> <![CDATA[i / (A·cm -2 )]]> Steel substrate (921A) -687 7.87E-6 Example 1 -437 2.35E-6 Example 2 -429 2.12E-6 Example 3 -454 2.98E-6
[0054] The prepared coating samples were subjected to room temperature dry sliding wear test. The quenched and low temperature tempered rolling bearing steel GCr15 and titanium alloy Ti6A14V were used as standard samples. The wear weight loss of the standard samples and the wear samples was measured by weighing method. The samples were wiped with alcohol before and after wear and the inductance was 10 -4 The sample loss weight is weighed on an electronic analytical balance (all results are the average of three identical samples), and the relative resistance ε, that is, the ratio of the standard sample weight loss to the sample weight loss, is used as a measure of the wear resistance of the sample.
[0055] Table 2 Room temperature dry sliding wear test results of titanium alloy cladding layer of Examples 1 to 3 and quenched rolling bearing steel GCr15
[0056]
[0057] Table 3 Room temperature dry sliding wear test results of titanium alloy cladding layers of Examples 1 to 3 and titanium alloy Ti6A14V
[0058] Cladding layer Example 1 Example 2 Example 3 Ti6A14V Before wear, g 7.9652 7.8845 7.8960 9.8009 After wear, grams 7.9515 7.8647 7.8776 8.8358 Wear loss, g 0.0137 0.0198 0.0184 0.9651 Relative wear resistance 70.45 48.74 52.45 1.0
[0059] It can be seen from the results in Table 1 above that the self-corrosion potential and self-corrosion current density of the cladding layer samples prepared in each embodiment are equivalent; it can be seen from Table 2 that the relative wear resistance of the titanium alloy coating is significantly improved compared with that of steel and titanium alloy, indicating that the cladding coatings prepared by this patent have a lower corrosion reaction driving force, a significantly smaller tendency to corrode, and significantly improved wear resistance.
[0060] The above content is a further detailed description of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to the above descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.
Claims
1. A method for preparing a titanium alloy coating on a steel substrate, characterized in that: The preparation method comprises the following steps: a. preparing titanium alloy powder; b. pretreating a steel substrate; polishing the surface of the steel workpiece, then ultrasonically cleaning it with clean water and ethanol for 20-25 minutes respectively, then drying it and preheating it in advance; c. uniformly coating the tin bronze powder on the surface of the steel substrate with a binder; d. preparing a copper transition layer on the surface of the steel substrate by laser cladding under argon protection, and then polishing the surface of the cladding layer by mechanical processing; e. uniformly coating the titanium alloy powder on the surface of the material treated in step d with a binder; f. preparing a titanium alloy coating on the surface of the steel substrate by laser cladding under argon protection; polishing the surface of the cladding layer by mechanical processing to complete the preparation of the titanium alloy coating.
2. The method for preparing a titanium alloy coating on a steel substrate according to claim 1, characterized in that: In step a, the titanium alloy powder is prepared from raw materials with the following weight percentages: Ni 40-50%, Fe 8-10%, Co 5-10%, Cr 5-10%, Nb 5-10%, and the balance is Ti; deionized water is weighed according to 1-10% of the weight percentage of the raw materials and placed in a dispersion tank, slowly stirred, and then a binder polyvinyl alcohol is added at 5-10% of the weight percentage of the raw materials until it is dissolved; metal powders of Ni, Fe, Co, Cr, Nb, and Ti are added in sequence according to the above proportions, high-speed grinding and dispersion are performed for 20-30 minutes, and drying treatment is performed at 120° C. for more than 2 hours to obtain a titanium alloy powder with a powder diameter between 45 and 105 μm.
3. The method for preparing a titanium alloy coating on a steel substrate according to claim 1, characterized in that: In step b, during the steel surface pretreatment, the workpiece surface is polished and cleaned using sandpapers of 100 mesh, 150 mesh, 250 mesh, 400 mesh and 600 mesh in sequence; and the steel substrate is preheated to 200°C.
4. The method for preparing a titanium alloy coating on a steel substrate according to claim 1, characterized in that: In step c, the tin bronze powder with a powder diameter of 50 to 100 μm is dried at 120° C. for more than 2 hours, and then the tin bronze powder is coated on the surface of the steel substrate using a polyvinyl alcohol adhesive.
5. The method for preparing a titanium alloy coating on a steel substrate according to claim 1, characterized in that: In step d, during the laser cladding process, the laser beam scans vertically, and argon gas is blown laterally for protection during the scanning process, and argon gas is blown coaxially to protect the lens barrel; the process parameters are: laser power 0.75-1.2KW, scanning speed 2.5-3.5mm / s, spot diameter 4mm, the distance from the laser mirror to the surface of the titanium alloy sample is 100mm, and the argon gas protection pressure is 0.3-0.7MPa.
6. The method for preparing a titanium alloy coating on a steel substrate according to claim 1, characterized in that: In step e, the titanium alloy powder is evenly coated on the surface of the steel substrate using a polyvinyl alcohol adhesive.
7. The method for preparing a titanium alloy coating on a steel substrate according to claim 1, characterized in that: In step f, during the laser cladding process, the laser beam scans vertically, and argon is blown laterally for protection during the scanning process. At the same time, argon is blown coaxially to protect the lens barrel. The process parameters are: laser power 0.75-1.5KW, scanning speed 2.5-4.5mm / s, spot diameter 4mm, the distance from the laser mirror to the surface of the titanium alloy sample is 100mm, and the argon protection gas pressure is 0.4-0.7MPa.
8. The method for preparing a titanium alloy coating on a steel substrate according to claim 2, characterized in that: In step a, a planetary ball mill is used for high-speed grinding and dispersion, with a rotation speed of 1000-1500 rpm.
Citation Information
Patent Citations
Corrosion resistant technique for steel structure
CN105420722A
Preparation method for improving wear resistance of titanium alloy composite coating
CN108118329A
Titanium alloy coating and preparation method thereof
CN112812589A
Steel-based titanium coating and preparation method and application thereof
CN113774374A
Slewing bearing gear tooth surface with wear-resistant coating and preparation method thereof
CN114086172A
Cited By
Bionic dentate interlaced interlocking structure coating as well as preparation method and application of bionic dentate interlaced interlocking structure coating
CN120272901A